2015
DOI: 10.1103/physrevlett.114.117603
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Origin of Giant Magnetoelectricity in Doped Y-type HexaferriteBa0.5Sr1.5Zn2(

Abstract: We investigated site-specific magnetic behaviors of multiferroic Ba 0.5 Sr 1.5 Zn 2 ðFe 1−x Al x Þ 12 O 22 using Fe L 2;3 -edge x-ray magnetic circular dichroism. The Al dopants mostly replace the Fe 3þ ions at octahedral (O h ) sites, which contribute unquenched angular momenta through off-centering displacements. This replacement greatly reduces the magnetic anisotropy energy to change the magnetic order from a helical to a heliconical type with enhanced magnetoelectric susceptibility (α ME ). The tetrahedra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, due to the quenched orbital moments in the tetrahedral and centered octahedral 31 , the p-d hybridization in Me5-8 and Me10 would be very weak, leading to the negligible polarization by this mechanism. But, the off-center Fe/Co in octahedral can induce large orbital moments 31 which may enhance the extent of p-d hybridization. Therefore, Me3, Me4, and Me9 sites may provide larger a0 and subsequently larger P via the p-d hybridization mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the quenched orbital moments in the tetrahedral and centered octahedral 31 , the p-d hybridization in Me5-8 and Me10 would be very weak, leading to the negligible polarization by this mechanism. But, the off-center Fe/Co in octahedral can induce large orbital moments 31 which may enhance the extent of p-d hybridization. Therefore, Me3, Me4, and Me9 sites may provide larger a0 and subsequently larger P via the p-d hybridization mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…31 , the p-d hybridization in Me5-8 and Me10 would be very weak, leading to the negligible polarization by this mechanism. But, the off-center Fe/Co in octahedral can induce large orbital moments31 which may enhance the extent of p-d…”
mentioning
confidence: 99%
“…It is well known that these calculations are accurate for X-ray energies away from the absorption edge. To estimate the penetration depth at the edge at 711 eV more precisely, we take into account the intensity ratio ~9.26 of the XAS spectrum 54 at the pre-edge and the absorption edge. The penetration depth is deduced to be 39 nm from dividing the depth at Ei = 702 eV by the XAS intensity ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Chun et al found that the critical magnetic field for switching a polarization can be significantly reduced from 1.0 T down to 1.0 mT in a properly Al-substituted system, as shown in Ba 0.5 Sr 1.5 Zn 2 (Fe 1−x Al x ) 12 O 22 [210,211]. A giant magnetoelectric susceptibility was observed in the sample with x = 0.08.…”
Section: Complex Hexaferritesmentioning
confidence: 96%